AIS scores in spine and spinal cord trauma: Epidemiological considerations. (28th February 2018) - Maiman, Dennis; Pintar, Frank; Malik, Waqar; Yoganandan, Narayan
ABSTRACT: Background : The Abbreviated Injury Scale (AIS) is an internationally accepted coding system created by the Association for the Advancement of Automotive Medicine, utilized to code traumatic injuries as a function of severity, the latter often defined as mortality risk. Periodic reassessment of that risk is prudent, in light of advances in health care and relationship of nonanatomic factors to death. Objective : The objective of this study was to reevaluate the risk of death associated with spine fractures with and without neurologic deficit, age factors associated with it, and the impact of hospital coding on the accuracy of these efforts. Methods : Medical records and imaging of patients treated at a level 1 trauma center from 2014 through 2016 with discharge International Classification of Diseases, 10th revision (ICD-10) diagnoses of spinal trauma and spinal cord injury (SCI) were reviewed. Data were collected on demographics, complications, neurologic status, and outcomes. Results : Three hundred seventy patients met the criteria for inclusion in this effort. Errors in ICD-10 discharge codes were seen in 45% of the cases, both false positive and negative. One hundred thirty-four patients, with a mean age of 45, were admitted with neurologic deficit. There were 8 SCI-related deaths; 2 were postoperative out of 110 undergoing surgical treatment. All deaths in this group were in patients with upper level SCI, with a mean age of 68. Ten patients had spontaneous neurologic improvement within 24 h. One hundred nineteen patients without deficit had AIS 2 scored fractures; there was one postoperative death out of 47 patients undergoing surgical treatment. One hundred seventeen patients without deficit suffered AIS 3 fractures; 66 underwent surgery without any deaths. There was one nonoperative death. Age and high quadriplegia were the only factors associated with mortality. Conclusions : Mortality risk in patients with deficit was associated more with age at injury than extent of anatomic injury. Spine trauma without neurologic deficit is benign in younger populations and AIS scores could be age adjusted. Mortality risk is higher in high cervical injuries with neurologic deficit and in the elderly. An incidental finding is that demographic studies based solely on discharge ICD coding may contain errors and should be considered critically.